Diabetic Ketoacidosis in Children - An Experience in a Tertiary Hospital (Ibrahim Medical College Journal, 2009)
A retrospective study was done in the in-patient department of paediatrics, BIRDEM from January 2002 to November 2006 to determine the clinico-laboratory features, precipitating factors and outcome of diabetic ketoacidosis. Over the five year period, 344 diabetic patients were hospitalized. Among them, 54 (15.6%) had diabetic ketoacidosis (DKA). Among those, 50 were Type I, one was Fibrocalculous Pancreatic Diabetes (FCPD) and 3 were of other specific types. More than half (51.9%) of the patients were newly diagnosed. Amongst the precipitating factors, 28% had missed insulin and 48% had overt infection. Infections, particularly those of the respiratory tract, were the main precipitating cause for the DKA. There was h/o both infection and missed insulin injections in 11.5% patients. The mean age of patients with DKA was 11.2 ± 4.4 years. Those in the age range 10-14 yrs suffered most frequently (p